Spread of animal diseases through international trade and the role of the border veterinary services in Brazil - de Sá, Marcos Eielson Pinheiro; de Melo, Cristiano Barros (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. de Sá M.E.P. & de Melo C.B. [Spread of animal diseases through international trade and the role of the border veterinary services in Brazil.] Disseminação de enfermidades animais por meio do comércio internacional e o papel dos serviços veterinários de fronteira no Brasil. Revista Brasileira de Medicina Veterinária, 38(1):7-12, 2016. Universidade de Brasília, Programa de Pós-Graduação em Ciências Animais, Campus Universitário Darcy Ribeiro, ICC Sul, Asa Norte, Brasília, DF 70910-900, Brasil. E-mail: cristianomelo@unb.br The international movement of animals and products of animal origin (PAO) is a major mechanism of introduction and spread of pathogens in disease-free areas. Aiming for prevention and control of diseases, the commercial transactions of animals and their products are carried through a series of technical regulations and must follow the international sanitary standards set by the World Organisation for Animal Health (OIE). The knowledge, management and control of the movement of live animals in Brazil are important tools to aid in the sanitary condition of the Brazilian herd, which is essential for the maintenance and expansion of the country’s participation in the global market. The satisfactory performance of governments and the credibility of the border veterinary services are essential components to successfully achieve the process of mitigating the risks associated with the spread of diseases through international trade.